2018
DOI: 10.1186/s12995-018-0185-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Consumption (V’O2) and physical Strainas measured by the occupational activity of cleaning personnel

Abstract: BackgroundThe aim of the study was to determine the physical effort and energy expenditure needed over a working period of 45–60 min, specifically for the occupational activity of cleaning. The effort was demonstrated in absolute terms (V’O2), in relation to the involved person’s maximum physical capacity (peak V’O2) and in relation to the individual aerobic-anaerobic threshold (V’O2 at VT1, the point when lactate starts to accumulate but can be cleared). In addition to this, the aim was to verify the suitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Eine eigene Studie [18] bediente sich dieser Methode zur Beschreibung der Arbeitslast und deren Bewältigung beim Reinigungspesonal in Reha-Kliniken auf der Insel Borkum (2018) 1 . Das Ziel der Studie war es, über einen Zeitraum von 45 -60 Minuten die Leistung und den Energieverbrauch zu bestimmen, der bei Reinigungsarbeiten (am Beispiel von Reha-Kliniken = Housekeeping) erforderlich ist.…”
Section: Aktivitätunclassified
“…Eine eigene Studie [18] bediente sich dieser Methode zur Beschreibung der Arbeitslast und deren Bewältigung beim Reinigungspesonal in Reha-Kliniken auf der Insel Borkum (2018) 1 . Das Ziel der Studie war es, über einen Zeitraum von 45 -60 Minuten die Leistung und den Energieverbrauch zu bestimmen, der bei Reinigungsarbeiten (am Beispiel von Reha-Kliniken = Housekeeping) erforderlich ist.…”
Section: Aktivitätunclassified
“…The energy consumed by the cleaners during work was estimated to be 4.12 ± 1.01 kcal min −1 . Although several studies have been performed on the aerobic capacity of domestic workers [ 17 , 18 , 40 ], no studies have yet been conducted to estimate energy consumption and heart rate during work [ 11 , 13 , 32 , 46 – 48 ]. In a survey conducted by Anjos et al [ 49 ] on Brazilian solid waste collection workers, the average energy consumed during work was estimated to be 5.4 ± 1.4 kcal min −1 , which is higher than the results of the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey conducted by Preisser et al on 65 municipality cleaners in three separate groups consisting of two separate waste collection workers and one group of Hamburg city cleaners in Germany, the mean oxygen uptake was estimated to be over 30% VO 2 -max in all participants [ 11 , 13 ]. In the same vein, Frohlich et al performed a study on cleaners in Hanover, Germany, and concluded that the physical workload of the staff exceeded the permitted level [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations